Statistical Survey on Household Consumption in the Context of Economic Growth and Decline - Molienė, Ona; Misiūnas, Algimantas (Lithuanian Journal of Statistics, 2010)
The article presents an in-depth analysis of household consumption expenditure in Lithuania in 2005−2008 through the use of not only traditional indicators and methods but also those proposed by the authors of the article. The results of the calculations might be useful in the analysis of the efficiency of the poverty and social inequality reduction policy. The purpose of the article is to reflect the socioeconomic stratification of society and its changes across the country, in urban and rural areas. In the survey, different – identification, secondary grouping, summary indicators, and index – methods were used. Traditional and elementary statistical indicators – an arithmetic mean, a mode, and a median – were used for the assessment of the asymmetry of the distribution of expenditure. In summarising structural differences in consumption expenditure, it is proposed to use the Gateva integral coefficient of structural differences; movement in this coefficient helps to reveal shifts in consumption patterns in household groups.The analysis carried out confirmed the assumption that the outbreak of the economic crisis in 2008 had a negative impact on the level and structure of household consumption expenditure, which was stronger in case of urban than rural households.
Keywords: none